Community housing: functional outcome of severe mental illness is associated with the personality traits of the case manager. Issue 2 (15th May 2019) - Lodder, Mandy; Schrijvers, A.J.P.; Leeuw, J.R.J. de; Brouwer, R.M.; Cahn, W.
Abstract : Purpose: The purpose of this paper is to examine whether there is an association between case managers' personality traits and functional outcome of people with severe mental illness (SMI) living in community housing programs (CHP). Design/methodology/approach: Functional outcome is measured by the extent of self-reliance. Self-reliance of people with SMI was measured with the Dutch Self-Sufficiency Matrix. The personality of the case manager was measured with the NEO Five Factor Inventory. Findings: Conscientiousness of case managers was associated with an increased self-reliance over a period of two years, in those with SMI living in CHP (OR.2.800 ρ = 0.04). Practical implications: When these findings are replicated, they could be used in the case managers selection process and/or training programs. Social implications: Conscientiousness of case managers was associated with functional outcome of persons with SMI living in supported housing and that female subjects benefitted the most. This study suggests that conscientious care planning is essential in the recovery process. Originality/value: No previous studies have been performed examining the specific relationship between the case manager's personality traits and functional outcome of people with SMI.